FUNGICIDAL ACTIVITY OF GARLIC (ALLIUM SATIVUM) BULBS EXTRACTS AGAINST PLANTS PHATOGENIC FUNGI - Khairan, khairan; Aulina, Aulina; Bahi, Muhammad; Nova Eriana, Cut; Sriwati, Rina (Universitas Lampung, 2019)
Fungicidal activity of garlic (Allium sativum) bulbs extracts against plants phatogenic fungi. Garlic (Allium sativum Linn) has been known to containing organosulphur compounds. These compounds are convinced to possess antibacterial, antifungal, and anticancer activities. The aim of this study is to determine fungicidal activity of garlic bulb extracts against some plants phatogenic fungi. The paper disc agar difussion technique was used to determine fungicidal activity of garlic bulbs extracts. The results showed that in general garlic bulbs extracts provides fungicidal activities. Calculated EC50 values indicated that ethyl acetate garlic bulbs extract was most active against Colletotrichum capsici, Fusarium oxysporum f. sp.capsici, and Sclerotium rolfsi by EC50 values of 48,6; 50,3; and 51.3% respectively. Meanwhile methanolic garlic bulbs extract was the most active against Sclerotium rolfsi with EC50 values of 24,3%.